Theoretical study on the application of isothermal compression technology in vapor‐compression refrigeration systems with an isothermal piston - Yu Hu (Wiley, 2021)
Abstract Vapor‐compression refrigeration systems are widely used in refrigeration equipment. Theoretically, the process is typically divided into two isobaric processes: an adiabatic isentropic compression process and adiabatic isentropic throttling process. The refrigeration compressor is the main energy‐consuming component in vapor‐compression refrigeration systems. However, this device has a large energy loss and low overall efficiency in the adiabatic isentropic compression process. In this study, a modified vapor‐compression refrigeration cycle with an isothermal piston is proposed to realize near‐isothermal compression of a refrigerator to significantly reduce the energy loss in the compression process and improve the system performance. A real‐gas compression process model is established, and the heat transfer index Hex is set. By changing the heat transfer index Hex, the performances of the vapor‐compression refrigeration system under ideal and real compression conditions are compared and analyzed. Compared with a traditional vapor‐compression refrigeration system, the coefficient of performance of the compressor with an isothermal compression process is increased by approximately 17%. The results also demonstrate that the lower the evaporation temperature Te and higher the condensation temperature Tc, the greater the optimization effect of the isothermal compression.